PUBLIC TRUST IN INSURANCE APPLICATION BASED : STUDY CASE IN TEMBILAHAN - Alda Putri Febriani; Nur zaitul Akma Akma; Helly Khairudin (Indragiri Research Center (ingreat), 2025)
The development of digital technology has encouraged the emergence of app-based financial services, including digital insurance. However, the level of public acceptance and trust in app-based insurance remains varied, particularly in areas such as Tembilahan. This study aims to determine and analyze public trust in app-based insurance in Tembilahan and the factors that influence it. This study used a qualitative approach with in-depth interviews and observations of people who are aware of or use app-based insurance. The results show that the level of public trust in app-based insurance is still in the sufficient category. Financial literacy and digital literacy play an important role in shaping public trust, while risk perception, particularly related to data security and clarity of the claims process, are the main inhibiting factors. In addition, ease of use of the application and transparency of services contribute to increasing public trust. This research is expected to be a consideration for digital insurance providers and related parties in increasing public trust in app-based insurance services. Keywords: App-based insurance; Public trust; Financial literacy; Digital literacy; Fintech.